Disorder‐specific versus generic cognitive‐behavioral treatment of anxiety disorders in children and young people: a systematic narrative review of evidence for the effectiveness of disorder‐specific CBT compared with the disorder‐generic treatment, Coping Cat. Issue 1 (February 2017) - Oldham‐Cooper, Rose; Loades, Maria
Abstract: Background: Coping Cat (CC), a generic cognitive‐behavioral intervention for anxiety disorders in children and young people, is recommended in the United Kingdom for social anxiety disorder (SAD), generalized anxiety disorder, separation anxiety (SA), and specific phobias (SP), with disorder‐specific approaches generally favored in treatment of anxiety disorders in adults. Objectives: To compare CC with disorder‐specific cognitive‐behavioral therapy (CBT) interventions based on anxiety‐related treatment outcomes. Study Selection: Primary research articles describing treatment of children and young people aged 7–17 for SAD, generalized anxiety disorder, SA, and SP, using CC or disorder‐specific CBT. Results: Ten studies implemented CC and four implemented disorder‐specific CBT. One study compared CC with a disorder‐specific approach. There was a lack of data to support use of CC in treatment of SPs. However, CC was equally effective as disorder‐specific treatments for SA and SAD. Conclusions: A lack of data exists for disorder‐specific CBT interventions compared to CC.